Analysis of Students’ Higher-Order Thinking Skills through the End-of-Year Summative Assessment (ASAT) in the IPAS Subject at the Elementary School Level - Nur Ngazizah; Rintis Rizkia Pangestika (BASICA, 2025)
This study aims to analyze the higher-order thinking skills (HOTS) of elementary school students through the End-of-Year Summative Assessment (ASAT) in the Natural and Social Sciences (IPAS) subject at SD Muhammadiyah Kutoarjo. The research approach employed a quantitative descriptive method with item analysis based on the Rasch model. The research subjects consisted of 64 fifth-grade students and 25 ASAT items from the 2023/2024 academic year. Data were analyzed based on difficulty level, discriminative power, and the distribution of thinking categories (LOTS and HOTS) in accordance with the revised Bloom’s taxonomy (Anderson & Krathwohl, 2016). The results indicated that 68% of the items fell into the lower-order thinking skills (LOTS) category, while 32% were classified as HOTS. Rasch analysis revealed an imbalance between students’ ability levels and item difficulty parameters (item–person map). These findings indicate the need for improved teacher assessment literacy in developing questions that better stimulate analytical, evaluative, and creative skills. The implications of this study contribute to the development of authentic assessment models in elementary schools in line with the spirit the Merdeka Curriculum, by integrating the principles of inquiry-based learning and transformative assessment to optimize the achievement of sustainable scientific thinking competencies.